Electronic Properties of a New All-Inorganic Perovskite TlPbI3 Simulated by the First Principles - Zhao Liu; Ting Zhang; Yafei Wang; Chenyun Wang; Peng Zhang; Hojjatollah Sarvari; Zhi Chen; Shibin Li (Nanoscale Research Letters, 2017)
Abstract All-inorganic perovskites have been recognized as promising photovoltaic materials. We simulated the perovskite material of TlPbI3 using ab initio electronic structure calculations. The band gap of 1.33 eV is extremely close to the theoretical optimum value. Compared TlPbI3 with CsPbI3, the total energy (−3980 eV) of the former is much lower than the latter. The partial density of states (PDOS) of TlPbI3 shows that a strong bond exists between Tl and I, resulting in the lower total energy and more stable existence than CsPbI3.